Tendências de qualidade de vida no trabalho e bem-estar dos colaboradores entre alunos do Curso de Administração da UFAM - Boga, Isabelle Lages (Brasil, 2024)
This study addresses Quality of Life at Work (QWL), a concept related to the physical, psychological, and social conditions of workers within an organization. It involves aspects such as health, safety, satisfaction, recognition, and development, reflecting on the well-being of employees, which manifests in happiness, motivation, engagement, and productivity at work. The overall objective is to analyze the benefits of promoting management oriented towards Quality of Life at Work. The methodology employed was basic research, with a descriptive objective and quantitative approach, using a questionnaire with convenience sampling. The results highlight the importance of quality of life at work and the well-being of employees with emphasis on aspects related to performance and competitiveness of organizations. These aspects should be constantly monitored, considering the various realities experienced by the participants. Regarding the benefits of promoting management oriented towards QWL in organizations, the research reveals that compensation and benefits are significant motivating factors. Challenges faced include excessive demand, while events and celebrations are QWL strategies adopted by companies.